In vitro assessment of Neuronal PAS domain 2 mitigating compounds for scarless wound healing - Clements, Adam; Shibuya, Yoichiro; Hokugo, Akishige; Brooks, Zachary; Roca, Yvonne; Kondo, Takeru; Nishimura, Ichiro; Jarrahy, Reza (Frontiers in Medicine, 2023)
Background: The circadian rhythm helps maintain physiological homeostasis, and disruption of the circadian rhythm can lead to impaired wound healing. Neuronal PAS domain 2 (NPAS2), a core circadian clock gene, is expressed in dermal fibroblasts and has been shown to play a critical role in regulating collagen synthesis. Previous studies showed that Npas2 knockout mice demonstrated faster dermal wound closure suggesting that Npas2 can be a novel therapeutic target for pathological scarring and wound healing. We have performed high throughput drug screening and identified five FDA-approved hit compounds that suppress NPAS2 expression in fibroblasts. In this study, we hypothesize that the therapeutic suppression of Npas2 by hit compounds will have two effects: 1) attenuated excessive collagen deposition and 2) accelerated dermal wound healing without hypertrophic scarring. Materials and Methods: To test the effects of each hit compound (named Dwn1, 2, 3, 4, and 5), primary adult human dermal fibroblasts (HDFa) were treated with either 0, 0.1, 1, or 10 μM of a single hit compound. HDFa behaviors were assessed by picrosirius red staining and quantitative RT-PCR for in vitro collagen synthesis, cell viability assay, in vitro fibroblast-to-myofibroblast differentiation test, and cell migration assays. Results: Dwn1 and Dwn2 were found to significantly affect collagen synthesis and cell migration without any cytotoxicity. Dwn3, Dwn4, and Dwn5 did not affect collagen synthesis. Dwn1 also attenuated myofibroblast differentiation on HDFa. Conclusion: Dwn1 and Dwn2 may serve as possible therapeutic agents for future studies related to skin wound healing.